Symptom Profile of Patients with Psychotic Disorders - Nepal, S.; Gupta, D.; Neupane, D. (Journal of Psychiatrists’ Association of Nepal, 2018)
Introduction: According to WHO, schizophrenia is a severe mental disorder affecting about 23 million people worldwide. Psychoses, including schizophrenia, are characterized by distortions in thinking, perception, emotions, language, sense of self and behavior. The impacts of these disorders are severe, with approximately 1 million people committing suicide annually. There is also an increase in co morbidity of these different conditions. So, this study was carried out to assess the symptom profile of patients with schizophrenia and other psychotic disorders (excluding mood disorders, substance induced psychotic disorders, organic psychotic disorders). Material and Method: Discharge record sheets of all cases admitted (Total 86) to the psychiatric ward over the study period were reviewed. Cases diagnosed as schizophrenia and other psychotic disorders were enrolled. Major symptoms were listed from the discharge papers. Results: Out of the total number of patients enrolled in the research, 68.6% were male while 31.4% were female. The mean age of the patients was found to be 31.03 years with a minimum age of 16 years and maximum 63 years. Most were from lower middle class family, Hindu by religion and unmarried. Among 86 cases, 26(30.2%) were diagnosed as Unspecified nonorganic psychosis, 24(27.9%) as Schizophrenia, 19(22.1%) as Schizoaffective disorder, 14(16.3%) as Acute & Transient Psychotic Disorder, 3(3.5%) as Persistent delusional disorder. Delusion of persecution was present in 46 cases (53.5%), Delusion of reference in 33 cases (38.4%) and Hallucinations in 32 cases (37.2%). Out of the 86 patients enrolled in the study, 15 (17.4%) had at least one suicidal attempt. Conclusion: Significant number of patients were diagnosed as Schizophrenia which is itself a chronic, debilitating illness. Hallucinations and delusions were present in most of the cases.